Case Report: Case of Wernicke’s encephalopathy complicated by postoperative gastroparesis following sigmoid colon malignant tumor surgery with a literature review - Qian, Zhengpeng; Wu, Dewang; Zhu, Chengzhang; Xu, Shiyun; Du, Binbin; Li, JingJing (Frontiers in Oncology, 2026)
ObjectiveTo explore the pathogenesis, clinical characteristics, and key points of the diagnosis and treatment of postoperative gastroparesis (POG) complicated by Wernicke’s encephalopathy (WE) after sigmoid colon malignant tumor resection so as to improve the understanding of Wernicke’s encephalopathy occurring after gastrointestinal surgery.MethodsThe clinical data of a patient who developed WE due to POG and prolonged fasting following sigmoid colon cancer resection were retrospectively reviewed, and a comprehensive analysis was conducted in combination with relevant literature.ResultsThe research team retrospectively analyzed a case of intestinal surgery complicated by gastroparesis and long-term fasting, with the patient subsequently presenting with neurological symptoms such as confusion and somnolence. Initially misdiagnosed as an energy deficiency or intracranial lesions, the diagnosis was confirmed by magnetic resonance imaging (MRI) and therapeutic response.ConclusionGastrointestinal dysfunction and poor nutritional absorption after sigmoid colon resection can induce Wernicke’s encephalopathy. Early clinical identification of this disease is particularly important. Postoperative nutritional management and monitoring of neurological symptoms should be emphasized to enable timely intervention.